An investigation of the security of passwords derived from African languages - Sishi, Sibusiso Teboho (Rhodes University, Faculty of Science, Department of Computer Science, 2019)
Password authentication has become ubiquitous in the cyber age. To-date, there have been several studies on country based passwords by authors who studied, amongst others, English, Finnish, Italian and Chinese based passwords. However, there has been a lack of focused study on the type of passwords that are being created in Africa and whether there are benefits in creating passwords in an African language. For this research, password databases containing LAN Manager (LM) and NT LAN Manager (NTLM) hashes extracted from South African organisations in a variety of sectors in the economy, were obtained to gain an understanding of user behaviour in creating passwords. Analysis of the passwords obtained from these hashes (using several cracking methods) showed that many organisational passwords are based on the English language. This is understandable considering that the business language in South Africa is English even though South Africa has 11 official languages. African language based passwords were derived from known English weak passwords and some of the passwords were appended with numbers and special characters. The African based passwords created using eight Southern African languages were then uploaded to the Internet to test the security around using passwords based on African languages. Since most of the passwords were able to be cracked by third party researchers, we conclude that any password that is derived from known weak English words marked no improvement in the security of a password written in an African language, especially the more widely spoken languages, namely, isiZulu, isiXhosa and Setswana.
Keywords: Computers -- Access control -- Passwords; Computer users -- Attitudes; Internet -- Access control; Internet -- Security measures; Internet -- Management; Data protection